Does the Internet Use Improve the Mental Health of Chinese Older Adults? - Xie, Lin; Yang, Hua-lei; Lin, Xue-yu; Ti, Shi-ming; Wu, Yuan-yang; Zhang, Shuo; Zhang, Si-qing; Zhou, Wan-li (Frontiers in Public Health, 2021)
Abstract Purpose: The Internet has become an important part of daily life. However, older adults in China remain digital refugees amid the rapid development of digital information technology. This study attempts to scientifically answer how Internet use affects the subjective welfare of older adults. Method: Using data from the 2014 and 2016 China Longitudinal Aging Social Survey (CLASS), a combination of ordinary least squares, ordered logit regression models, and propensity score matching models were used to analyze the effects of Internet use on the mental health of Chinese older adults. Results: Our findings suggest that Internet use affects the mental health of older adults and increases the incidence of their depressive symptoms. These findings are robust to changing the key indicators, research method, and sample. Further heterogeneity analysis reveals that the negative effects on mental health are more evident for specific groups of older adults, such as those who are females, younger and middle-age, high-income, non-rural Hukou, less educated, and living with others. Conclusions: Cultivating the ability of older adults to use the Internet and maintain a rational attitude while doing so can prevent its negative impact on their life satisfaction. Moreover, it can improve their attitudes towards using the technology, and reduce their anxiety.